Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1590/s1519-566x2005000200024
|View full text |Cite
|
Sign up to set email alerts
|

Does Barypenthus concolor Burmeister (Trichoptera: Odontoceridae) select particles of different sizes for case building?

Abstract: Neotropical Entomology 34(2): 337-340 (2005) Barypenthus concolor Burmeister (Trichoptera: Odontoceridae) Seleciona Partículas de Diferentes Tamanhos Para a Construção de Casulos?RESUMO -Larvas de muitas espécies de Trichoptera utilizam partículas orgânicas ou inorgânicas para construir seus casulos nos quais ficam protegidas de predadores. O estudo da grande variedade de estruturas produzidas por tricópteros é muito importante para o entendimento da evolução do comportamento de construção de casulos. O obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…They construct typical odontocerid cases of sand grains and probably exhibit the typical habitat preferences and mode of living. The larvae of Barypenthus concolor do not select specific particle sizes for case building ( Moretti and Loyola, 2005 ).…”
Section: Catalogmentioning
confidence: 99%
See 1 more Smart Citation
“…They construct typical odontocerid cases of sand grains and probably exhibit the typical habitat preferences and mode of living. The larvae of Barypenthus concolor do not select specific particle sizes for case building ( Moretti and Loyola, 2005 ).…”
Section: Catalogmentioning
confidence: 99%
“…— Paprocki et al, 2004 :14 [checklist]. — Moretti and Loyola, 2005 :337 [larva; biology]. — Dumas et al, 2009 :371 [distribution].…”
Section: Catalogmentioning
confidence: 99%
“…According to some authors, the type of organic material used by caddisflies for case-building may vary depending on its abundance (Hanna, 1961;Otto & Svensson, 1980). Moreover, Moretti & Loyola (2005) demonstrated that larvae of Barypenthus concolor, a tube-case-building trichopteran, use particle sizes in the same proportions as they are available in the habitat to build their cases. All these findings imply great selective pressure operating on this behaviour.…”
Section: Leaf Combinationmentioning
confidence: 99%